Morpho-physiological-based selection criteria for chili (Capsicum annuum) under drought stress during vegetative to generative phase - PENI LESTARI; MUHAMAD SYUKUR; TRIKOESOEMANINGTYAS TRIKOESOEMANINGTYAS; WAHYU WIDIYONO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Istiqomah I, Isnansetyo A, Murwantoko, Handayani DP, Lestari YN, Taslihan A, Permana IGN, Wijayanti E. 2023. Antibiotic resistance of emerging pathogenic bacteria of hybrid grouper farming in Indonesia. Biodiversitas 24: 2493-2501. A hybrid grouper is among the main coastal farming species in Asian countries, yet vibriosis is still a significant issue. Therefore, a knowledge of pathogenic strains responsible for recent cases is essential for developing appropriate control measures. The purpose of the study was to describe emerging bacterial pathogens associated with hemorrhagic disorder, skin wounds, and mortality in cantang hybrid grouper farms in Indonesia. A total of 30 bacterial strains were recovered from the kidney of diseased grouper on TCBS agar. Based on the ability to induce clinical signs and mortality of grouper juveniles owing to intraperitoneal bacterial infection at 106 CFU/fish, the bacteria were divided into three groups: pathogenic (n=11), low-pathogenic (n=2), and non-pathogenic (n=17). The pathogenic strains were putatively identified as Photobacterium damselae subsp. damsela (n=8), Vibrio alginolyticus (n=1), Vibrio harveyi (n=2), and Vibrio azureus (n=2) based on the biochemical characteristics and 16S rRNA and DNA gyrase B subunit gene sequences. The pathogenic bacteria were sensitive to erythromycin, gentamycin, oxytetracycline, and kanamycin. However, it still has various resistant patterns to ampicillin, fosfomycin, chloramphenicol, streptomycin, rifampicin, and enrofloxacin. This study demonstrated the emergence of pathogenic P. damselae subsp. damselae, Vibrio alginolyticus, V. harveyi, and V. azureus in grouper aquaculture in Indonesia with multiple antibiotic resistance, which needed to further studies.